The role of primary lymph node sites in survival and mortality prediction in Hodgkin lymphoma: a SEER population‐based retrospective study. (9th March 2018) - Ebied, Amr; Thanh Huan, Vuong; Makram, Omar Mohamed; Sang, To Kim; Ghorab, Mohamed; Ngo, Huyen Thi; Iraqi, Ahmed; Kamel, Mohamed Gomaa; Dang, Tran Ngoc; Vuong, Nguyen Lam; Hirayama, Kenji; Huy, Nguyen Tien
Abstract: As diagnostic and therapeutic modalities for Hodgkin's Lymphoma (HL) continue to improve, patient‐related factors affecting survival become more difficult to identify. Very little is known about the relationship between the primary site of lymph node (LN) involvement and survival of HL patients. We retrospectively analyzed the United States Surveillance, Epidemiology and End Results (SEER) database for 12, 658 HL patients reported between 1973 and 2010 using survival analysis and time‐interval multiple logistic regression (MLR) to disclose that relationship. The effect of all primary LN sites on the survival of HL patients was supported. The intra‐abdominal (IAB) primary LN site was significantly associated with the worst survival. The pelvic (P) LN sites were significantly and independently associated with nearly 2 times and 2.5 times the probability of having 1‐year overall mortality (OM) and 1‐year cancer‐specific mortality (CSM), respectively. Head, face and neck (HFN) primary LN sites were significant and independent predictors of better overall and HL‐specific survival. A worse survival with the intra‐abdominal primary LN site was probably related to their association with higher age, or advanced stages of HL. The biological basis behind the aggressiveness of intra‐abdominal and pelvic LN sites is yet to be investigated. Abstract : Little is known about the role of primary lymph node sites in survival in Hodgkin lymphoma (HL). This study uses a huge population‐based cohort using the SEER database. It was found that intra‐abdominal LN sites predict the worst survival in HL patients and that pelvic LN sites were the most aggressive in predicting HL‐specific 1‐year mortality, and hence, we recommend that primary LN sites be added to future international prognostic scores for HL.